CULTURAL RELATIONS BETWEEN CHINA AND CENTRAL ASIA IN THE BELT AND ROAD INITIATIVE CONTEXT - Wang Guilian, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
This abstract encapsulates the comprehensive exploration of cultural relations between China and Central Asia within the framework of the Belt and Road Initiative (BRI). The BRI, a monumental international development initiative proposed by China, seeks to enhance connectivity and cooperation among nations, with Central Asia occupying a pivotal role due to its historical ties and strategic location along ancient trade routes. Delving into historical contexts, the paper highlights the profound cultural exchange facilitated by the ancient Silk Road, establishing a historical foundation for modern-day interactions between China and Central Asia. Emphasizing cultural exchange, economic cooperation, educational collaborations, and heritage preservation initiatives, it outlines the multifaceted efforts aimed at fostering mutual understanding, preserving heritage, and promoting academic exchange between the regions. Acknowledging existing challenges such as linguistic barriers and divergent cultural practices, the abstract underscores these obstacles as opportunities for dialogue and mutual learning. It underscores the transformative potential of investments in cultural projects and academic endeavors in deepening cultural ties. The abstract concludes by envisioning a promising future wherein the Belt and Road Initiative acts as a catalyst for strengthening cultural relations. By embracing diversity, nurturing academic exchanges, and fostering a shared cultural heritage, China and Central Asia are poised to cultivate a more interconnected and harmonious relationship, thereby contributing to the broader objectives of the Belt and Road Initiative.